1986
DOI: 10.1128/jb.166.1.20-28.1986
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and nucleotide sequence of a DNA fragment from Bacillus natto that enhances production of extracellular proteases and levansucrase in Bacillus subtilis

Abstract: A DNA fragment from Bacillus natto IF03936 has been cloned which enhances the production of both extraceilular alkaline and neutral proteases in Bacillus subtilis. The DNA sequence analysis around the gene responsible for the hyperproduction, prtR, revealed one open reading frame (comprising 60 amino acid residues) which was bounded by potential transcriptional and translational regulatory signals in its preceding and following regions. This open reading frame was not homologous to the published sequences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
78
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 61 publications
2
78
0
Order By: Relevance
“…Several regulatory genes encoding small polypeptides of 46 to 65 amino acid residues which cause a higher level of expression of a class of extracellular proteins in B. subtilis have been reported, i.e., senS (45), degR (25,42,49), and degQ (3,48). The pleiotropic effects of these genes suggest that they are part of a global control mechanism affecting the synthesis of degradative enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several regulatory genes encoding small polypeptides of 46 to 65 amino acid residues which cause a higher level of expression of a class of extracellular proteins in B. subtilis have been reported, i.e., senS (45), degR (25,42,49), and degQ (3,48). The pleiotropic effects of these genes suggest that they are part of a global control mechanism affecting the synthesis of degradative enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of degQ was shown to be controlled by DegS-DegU. This Production of a class of degradative enzymes in Bacillus subtilis, including an intracellular protease and several secreted enzymes (levansucrase, alkaline and metalloproteases, a-amylase, 3-glucanase[s], and xylanase) (3,5,11,29), is controlled at the transcriptional level by the DegSDegU two-component system and by at least two additional regulatory genes, degQ and degR, which encode small polypeptides of 46 and 60 amino acids, respectively (3,25,42,48,49).Although the two-component system is required for degradative enzyme production, the products of degQ and degR appear to be dispensable (48,49). Mutations were identified in both degS and degU leading to either deficiency of degradative enzyme production or a pleiotropic (Hy) phenotype, which includes hyperproduction of degradative enzymes, ability to sporulate in the presence of glucose, decreased genetic competence, and loss of flagella (6,12,17,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple copies of the degR (30,42,50), degQ (2,49), senS (46), and tenA (33) genes result in the overproduction of the extracellular proteases. On the other hand, the abrB (10), hpr (35), sin (12), and pai (16) loci are involved in negative regulation, and overproduction of the products of these genes inhibits the production of the exoproteases.…”
mentioning
confidence: 99%
“…The production of the exoproteases is also subject to additional positive and negative regulation by several factors (20,26). One such factor is degR, which in multicopy causes overproduction of extracellular proteases and in single copy contributes to positive regulation of aprE (subtilisin) expression (28,29,33,55). DegR is a 60-amino-acid polypeptide with homology to the N-terminal region of DegS (36), and it has been shown that multiple copies of degR stabilize the phosphorylated form of DegU (28).…”
mentioning
confidence: 99%